Management style of educational and medical centers in Qazvin: Perception of frontline staff from the structure and condition - Sogol Sarikhani; Omid KHosravizadeh; Bahman Ahadinezhad; Mohammadreza Mohammadkhani; Fateme Vahdati; Rana Soheylirad (Tehran University of Medical Sciences, 2021)
Introduction: Management is one of the most important factors that can affect the performance of an organization such as hospital. Therefore, identifying the management style used in hospitals can be useful empirical evidence to solve many hospital problems. In this study, the management styles used in the educational-medical centers of Qazvin University of Medical Sciences have been studied and determined. Methods: In this descriptive-analytical study, a sample of 411 people was selected using random sampling method from a population of 2265 employees working in university hospitals in Qazvin. The required data were collected using a valid Clark management style questionnaire and through employee perception survey. Finally, the obtained information was analyzed in the space of STATA 15 and SPSS 16 software. Results: Individuals reported the highest frequency (42%) for autocratic style items and the lowest frequency (25%) for delegating style items. Autocratic style had the highest total mean (3.22 of 5) and delegating style had the lowest total mean (2.87 of 5). Apart from autocratic style, there was a significant difference between hospitals in terms of the use of participative and delegating styles (p <0.05). Conclusion: In all hospitals, the dominant management style was autocratic style. It is suggested that managers be taught about the techniques and functional benefits of participative and delegating styles.